Simulação de malha triangular: um estudo sobre a adaptatividade da malha - Oliveira, Suzana Matos França de (2013)
In the last decades, cloth animation has been the focus of much research, due to demands from the entertainment industry and from e-commerce. That type of animation is most often the result of a physics-based simulation and has a great computational cost. This work investigates how to reduce the computational cost of the simulation, by refining the mesh only in regions that need a fine level of detail. The fabric model consists of a triangular mesh and uses a spring-mass-damper system to compute the forces among the particles, which are located at the mesh’s vertices. The collision detection depends on the arrangement of the cloth model and the objects in the scene. The mesh is refined or simplified, taking into account the spring compression, collision and curvature, so the simulation uses a better mesh every time step. Therefore, this work’s main objective is to study the dynamic behavior of cloth, using a remeshing procedure in order to adapt the mesh.